Implementasi Smart class Pada Ruang Belajar Di Jurusan TeknikElektro Berbasis RFID - Hikmatul Amri; Adam; Agustiawan; Hardi B; Iman Saputra; Rodotul Azkia; Suci Damayanti; Endang Setio Rini (ABEC Indonesia, 2022)
Electrical energy is one of the most important human needs and cannot be separated from daily needs. Lack of electrical energy can interfere with human activities as well. Therefore, the availability of electrical energy must be maintained. In Indonesia, the need for electrical energy is increasing because it is seen from population growth and advances in information and technology. The use of electric power is usually more widely used in the study rooms at the Bengkalis State Polytechnic, especially the Electrical Engineering Department consisting of classrooms, and laboratories and electrical workshops. In this study room, the electrical installation system is still conventional to turn on the lights, air conditioning and laboratory equipment centered on the panels in each room. Problems arise when room users do not turn off electrical equipment after the lecture is over and leave the room. The wasted use of electrical energy in the study room can be minimized by updating the conventional control system to semi-automatic. The system applied is smart door and smart class is an access to the electrical system by attaching the RFID card of lecturers who enter the class to the RFID access control. The test results show thatRFID access control detects RFID cards up to a distance of 6 cm. The exit button uses a low activation system where when pressed the output voltage is 1.10 volts and when released the output voltage is 17.41 volts. The electric bolt lock terminal voltage when active is 0 volts and when not active is 14.18 volts. The activation time of the RFID reader switch is 1.08 seconds and the deactivation time is 29.51 seconds. The system can work with a 100% success rate and an average execution time of 2.27 seconds.